Untidy origins : a story of woman's rights in antebellum New York - Ginzberg, Lori D. (The University of North Carolina Press, 2005)
In 1846 - two years before the Seneca Falls convention that launched the movement for women's rights in the US - six women in upstate New York petitioned their state's constitutional convention, demanding "equal, and civil and political rights with men". Who were these women, and does their story change the story of women's rights?